Motivos atribuídos por mulheres ao abuso de substâncias psicoativas - Soccol, Keity Laís Siepmann (2014)
The abuse of psychoactive substances interferes negatively on women's health, causing problems in various spheres of life in the world. As a result, this study aimed to understand the reasons why women assigned to the abuse of psychoactive substances. It is a qualitative research, phenomenological in nature based on theoretical-methodological Alfred Schütz, held at the Alcohol and Drugs Psychosocial Care Center "Caminhos do Sol" in the municipality of Santa Maria, Rio Grande do Sul, Brazil. The participants of the research were women who abuse psychoactive substances, ranging in age from 25 to 56 years old, doing treatment in this service. The production of the data occurred in the months of May and June 2013, through the phenomenological interview, which was recorded and was closed with the sufficiency of meanings. It was developed the comprehensive analysis and interpretation of the statements, in which elaborate steps were used by an author in the field of nursing which is a national reference of Social Phenomenology of Alfred Schütz. Ethical aspects have been complied with, in accordance with resolution nº 196/96 of the National Health Council. In the comprehensive analysis of typical action of women who abuse psychoactive substances, were care for two concrete categories: The first was the influences of social relations for the use/abuse of psychoactive substances that unveiled the influence of family, companions and friends both to the beginning of the use of psychoactive substances, as in abuse and relapse. The second was the conflicting family relationships and losses as fuse for the abuse of psychoactive substances that revealed that women have experienced family troubled relations, assaults, financial difficulties, losses due to death of relatives and companions, removal of conviviality with family, betrayal by the companions and loss of their dreams. It is hoped that this study will provide subsidies for activities of health professionals, as they can plan strategies of care according to the everyday needs of women. Still, it contributes to the family and to society, so that they can carry out concerted actions, and thus, acting directly on prevention of psychoactive substance abuse by women.